The Impact Of Economic Recession On Delhi's Hotel And Restaurant Industry: A Comprehensive Analysis ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: The hotel and restaurant industries wield a pivotal influence on the global economy, but they are exquisitely  vulnerable to economic oscillations. Comprehending the economic reverberations on these sectors is paramount for  formulating efficacious strategies to surmount obstacles and perpetuate growth. Objective: This paper scrutinizes the  economic repercussions on the hotel and restaurant industries and probes the factors that sway their performance  amidst economic recessions. It also investigates the organizational practices and stratagems implemented to grapple  with recessions and ensure survival. Methodology: Cross sectional field survey was executed in Delhi, India, with data  amassed from 10 five-star hotels and 30 quick-service restaurants employing a questionnaire. Respondents were in age  bracket of 31-50 years in which 70% were male and 30% of the respondents were manager. Chi-square tests, mean  calculations, standard deviation calculations, and t-tests were deployed for data analysis. Result: The results unveil  momentous associations between factors such as recession causes, severity of impact, measures adopted to combat the  recession, and strategies embraced subsequent to the recession. Additionally, the study examines expectations regarding  recovery time and organizational practices for retaining employees during a recession. Conclusion: The findings yield  invaluable insights into the industry's response to economic recessions and proffer guidance for hotel and restaurant  proprietors, managers, and staff to augment their competitiveness and navigate arduous economic circumstances.
Keywords: Delhi; Economic Impact; Global Recession; Hospitality Industry; Hotel; Restaurant